2010
DOI: 10.1016/j.rbmo.2009.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Altered first-trimester screening markers after IVF/ICSI: no relationship with small-for-gestational-age and number of embryos transferred

Abstract: First-trimester serum markers in 110 in-vitro fertilization (IVF) and 331 intracytoplasmatic sperm injection (ICSI) pregnancies were compared with 1431 pregnancies with spontaneous conception. Alterations of serum markers were evaluated with respect to small-for-gestational-age (SGA) growth and number of embryos transferred. For pregnancy-associated plasma protein A (PAPP-A), significantly lower concentrations were observed in IVF and ICSI pregnancies compared with controls (0.86 and 0.9 versus 1.06; P<0.001).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 55 publications
5
30
2
Order By: Relevance
“…4,[29][30][31][32][33] Some previous studies have also found decreased levels of PAPP-A in the subgroup of IVF pregnancies. 4,[30][31][32]34,35 In FET pregnancies, PAPP-A concentrations were unaffected when compared with those in the natural conception in several previous studies. 29,30,32,36 However, two previous studies showed that PAPP-A levels were decreased in FET pregnancies, but only in FET cycles accompanied by any hormonal treatment.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…4,[29][30][31][32][33] Some previous studies have also found decreased levels of PAPP-A in the subgroup of IVF pregnancies. 4,[30][31][32]34,35 In FET pregnancies, PAPP-A concentrations were unaffected when compared with those in the natural conception in several previous studies. 29,30,32,36 However, two previous studies showed that PAPP-A levels were decreased in FET pregnancies, but only in FET cycles accompanied by any hormonal treatment.…”
Section: Discussionmentioning
confidence: 83%
“…35 However, Bender et al found no correlation between altered serum marker levels of PAPP-A and fβ-hCG and transfer of one, two, or three embryos in ART pregnancies. 31 Infertility itself and its severity may also be the reason for altered PAPP-A levels. In fact, one previous study found that in pregnancies conceived naturally after a time greater than 2 years, PAPP-A levels were decreased similarly than in IVF pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies showed decreased PAPP-A levels in ART pregnancies combined with unaltered levels of fβ-hCG [9,13,14,16,17,20,21] increased fβ-HCG levels [12,22,23,24] or even decreased fβ-hCG levels [15,25]. Two studies reported only an increase in fβ-hCG levels [10,26], and some studies reported no changes in maternal serum values in ART pregnancies [11,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In ART pregnancies maternal serum marker levels change during the first trimester affecting the risk assessment for DS [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Counseling for prenatal screening of women carrying an ART pregnancy is complicated due to contradictory reports in FTS performance in ART pregnancies.…”
Section: Introductionmentioning
confidence: 99%